Improving MSME Performance Based on Digital Marketing, Intellectual Capital, Product Innovation and Competitive Advantage - Arista, Sintha Wahyu; Hermawan, Sigit (Jurnal Manajemen Bisnis, 2025)
Research aims: Using influence and route analysis tests, this study will examine how digital marketing, intellectual capital, item innovation, and competitive advantage have been used to boost the achievement of micro, small, and medium-sized enterprises (MSMEs).Design/Methodology/Approach: The researchers in this study used a quantitative research strategy based on survey data. Due to its sheer size and employment density, the food and beverage industry in East Java is chosen as the study's population of micro, small, and medium-sized enterprises (MSMEs). Probability sampling is the method used for the sampling. Various tests are employed in data analysis, including validity, reliability, hypothesis, and route analysis.Research findings: Based on the findings, digital marketing, intellectual capital, and item innovation are factors that impact MSME achievement and competitive advantage to a lesser extent. Furthermore, MSMEs' success is partially impacted by digital marketing, intellectual capital, and item innovation, all of which contribute to their competitive edge.Theoretical Contribution/Originality: This study addresses a gap in the literature by investigating the factors that contribute to the improvement of achievement for micro, small, and medium-sized enterprises (MSME), specifically looking at the effects of digital marketing, intellectual capital, and item innovation. Here, variables such as market domination, new item development, IQ, and internet advertising come into play. By exploring how this generation's digital marketing and intellectual capital function, the study adds to the field's knowledge.Practitioners/Policy Implications: Findings from this research stress the need for a multi-faceted strategy to boost MSME performance, rather than a singular emphasis on digital marketing, ICM, item innovation, and competitive advantage. With this in mind, it is anticipated that MSME players would devise plans that incorporate these four aspects in order to improve market competitiveness and welfare.Research Limitations/Implications: Although the results are significant, there are a number of caveats to this study. It is possible that the study's geographical scope and the industries it examined are too narrow. The success of micro, small, and medium-sized enterprises (MSME) in areas such as digital marketing, IP, item innovation, and competitive advantage could differ in different regions and sectors. Hence, due to variations in technical infrastructure, resources, and markets, it is possible that not all MSMEs or locations may be completely served by this study's findings.